Heterocyclic imidazo-anthraquinone as an optical sensor: synthesis, characterization and evaluation of the chemosensory ability - Ferreira, Rosa Cristina Moutinho (2017)
Resumo da comunicação eletrónica apresentada na 21st International Electronic Conference on Synthetic Organic Chemistry, 1–30 November 2017; Sciforum Electronic Conference Series, Vol. 21.